STATUS HUKUM KEPEMILIKAN HAK ATAS TANAH MELAMPAUI BATAS MASYARAKAT ADAT DAYAK LUNDAYEH DESA BERIAN BARU DI KRAYAN BARAT KABUPATEN NUNUKAN PROVINSI KALIMANTAN UTARA (DITINJAU DARI UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR - Abdul Mu'min; Dewi Angelia Daniel (Yuriska: Jurnal Ilmiah Hukum, 2022)
The legal status of ownership of land rights is as regulated in the basic agrarian law number 5 of 1960 article 7 which reads: "In order not to harm the public interest, land ownership and control that exceeds the limit is not allowed". But what about the legal status of land ownership that extends beyond the boundaries of the Dayak Lundayeh Indigenous community in Berian Baru Village? And what is the obstacle for the government of Nunukan Regency in the context of returning the maximum land limit that exceeds the limit?. The method that the authors use in this study is Empirical Legal research, which is a legal research method using empirical facts arising from human behavior, both verbal behavior obtained from interviews and real behavior carried out through direct observation. The results of the study show that the legal status of land rights ownership of the Dayak Lundayeh indigenous peoples in the village of Berian Baru which exceeds the maximum limit will later be determined by the customary apparatus to be returned to customary land rights or jointly managed land which will benefit the indigenous people themselves. In writing this thesis, the author tries to provide an explanation of the legal status of ownership of land rights beyond the boundaries of the Dayak Lundayeh Indigenous community in Berian Baru Village.